As “Novas” Mídias e as Rotinas Produtivas dos Cadernos de Economia do Jornal da Paraíba e Correio da Paraíba - Avelar, Hallita Amorim Cézar Fernandes e (2015)
This dissertation proposes to study the productive routines and journalistic practices of nowadays in economics journalism, modified by technological innovations of recent years. The creation and popularization of the Internet, by itself, marked the twentieth century communication, shortening distances and expanding the journalist‟s universe, but the current phenomenon is the increasing number of new platforms, media and softwares available in the market. There are smartphones, tablets and apps, which, added to the wide range of possibilities that the internet provides, completely changed the language and practices of journalism. Aiming to analyze these issues, we study how, nowadays, the production of content works on the editorship of the Jornal da Paraíba and Correio da Paraíba, trying to understand the transformations which the journalistic production in this section has been submitted to in this new reality.